Pancasila Dan Hak Asasi Manusia: Perspektif Menuju Manusia Yang Adil Dan Beradab - Zainudin Hasan; Dodi Setiawan; Angga Bela Dinata; Erlangga Adnus; Andre Agape Lumban Gaol (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses the role of Pancasila in interpreting human rights and its implications in building a just and civilized society. The background covers the importance of Pancasila as the foundation of Indonesia's state ideology. The problem formulation is how Pancasila interprets human rights and its implications for the development of a just and civilized society. The discussion highlights the interpretation of each Pancasila principle regarding human rights and its impact in creating an inclusive and just environment. The conclusion is that Pancasila provides a solid philosophical foundation for the recognition and protection of human rights, ensuring that every individual has the right to live in freedom, equality, and dignity, in accordance with Pancasila values. It is hoped that understanding and applying Pancasila values can help build a just, civilized, and prosperous society.